Analisis Kesadaran Wajib Pajak dalam Kepatuhan Pembayaran Pajak UMKM Jawa Barat Pada Pengguna Platform E-Commerce - Suhono Suhono; Adhi Rizal; Reminta Lumban Batu; Seva Madjid (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research needs to be conducted to find out how much influence taxpayer awareness has on compliance with MSME tax payments on platform usersecommercein West java. The existence of this study aims to see how much the level of awareness of taxpayers, especially MSME actors in West Java, uses the platformecommerce in carrying out its business activities in compliance with paying taxes. The data source in this study is primary data in the form of a questionnaire that has collected 106 respondents as measured using a Likert scale. As for the research conducted using a data analysis model in the form of multiple linear regression analysis using SPSS tools. The results show that of the four dimensions of taxpayer awareness that can affect taxpayer compliance, one of which is the perception of the taxpayer partially does not have a significant effect on taxpayer compliance. However, the other three variables, namely tax knowledge, taxpayer characteristics, and tax socialization have a positive and significant effect on taxpayer compliance.